PENGARUH HARGA DAN VARIASI PRODUK TERHADAP LOYALITAS KONSUMEN DENGAN LINGKUNGAN USAHA SEBAGAI VARIABEL MODERATING (Studi Pada Usaha Perorangan Toko Rahma Muslimah Hijab dan Syar’i) - Afia Rohmatul, Vivi Afia Rohmatul; Wahyuni, Ika; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2025)
The aim of this research is to analyze the influenceThe Influence of Service The purpose of this study is to analyze the influence of variables Influence Price and Product Variation on Consumer Loyalty with Business Environment as a Moderating Variable (Study on Individual Business